KEPENTINGAN INDONESIA DALAM FORUM GLOBAL OCEAN ACTION SUM-MIT FOR FOOD SECURITY AND BLUE GROWTH TAHUN 2014 - Nike Afriati; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study is an article that will explain the importance to be achieved by Indonesia in its involvement as a partner country in the world maritime forum titled Global Ocean Action Summit 2014 organized by the Dutch Government in collaboration with FAO and the World Bank. Maritime conference is to discuss the action to be taken by the international communi-ty in addressing environmental issues, especially the environment and marine ecosystems. The vast oceans of the world is currently experiencing a serious threat which is one of the impacts of climate change. In addition, the conference also discussed how to implement the economic model oriented development environment such as that carried by Indonesia in this forum is the economic model blue.This study is a literature study. This study uses perspectives and theories of liberalism and the concept of national interest expressed by Jack C. Plano and Olton Roy.Results from this study indicate that Indonesia is actively involved in the marine world forum organized by the Netherlands in 2014 as a partner country aims to introduce and invite the international community to apply economic models of development oriented to the preservation of the marine environment as implemented by Indonesia that the economic model blue. This objective is to be achieved by Indonesia that Indonesian marine fisheries sector and become better with the cooperation with the international community.Keywords: Global Ocean Action Summit, Blue Economy, Cooperation, National Interest